2001
DOI: 10.1111/1468-0009.00222
|View full text |Cite
|
Sign up to set email alerts
|

Does the Chronic Care Model Serve Also as a Template for Improving Prevention?

Abstract: Practical models of ways to enhance service delivery are sorely needed to help close the gap between research and practice. An evidenced-based model of chronic-illness management is shown to apply equally to preventive interventions. Successful examples of prevention programs in cancer screening and counseling for health behavior change illustrate the utility of the model for prevention and across different types of health care organizations. Although there are some important differences between interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
312
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(322 citation statements)
references
References 84 publications
1
312
0
9
Order By: Relevance
“…Some have suggested that health care providers do not often think about prevention in those with disabilities 9 or chronic illness. 1,10 The results of this survey demonstrate that veterans with SCI want to discuss these issues. Of interest, although subjects did want to discuss diet and exercise, the majority of patients did not indicate a desire to discuss obesity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some have suggested that health care providers do not often think about prevention in those with disabilities 9 or chronic illness. 1,10 The results of this survey demonstrate that veterans with SCI want to discuss these issues. Of interest, although subjects did want to discuss diet and exercise, the majority of patients did not indicate a desire to discuss obesity.…”
Section: Discussionmentioning
confidence: 88%
“…1 The Chronic Care Model is a conceptual system of care that integrates elements of a health system organization to promote productive interactions between an informed activated patient and a prepared practice team. 2 VA leadership supports care for veterans with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Deux des modèles prennent cependant en compte les milieux de vie des patients et intègrent une dimension éducative [16,17].…”
Section: Résultatsunclassified
“…However more steps have to be implemented in order to provide the right level of prevention of chronic conditions. The application of the chronic care model would be beneficial in this respect with a greater control of patients, a greater role of nurses in primary care, and more resources devoted to provide information on the conditions identified in chronic patients (Glasgow et al, 2001). …”
Section: Pathways Towards the Optimal Modelmentioning
confidence: 99%